2014
DOI: 10.1002/cb.1498
|View full text |Cite
|
Sign up to set email alerts
|

Customer's perceived value of waiting time for service events

Abstract: The authors address the effects of money gain and loss on individually perceived value as predicted by prospect theory in a time gain‐and‐loss context. Three experiments were conducted. Experiment 1 results support the prospect theory concept of value function. According to Experiment 2 results, the amount of money involved exerted different impacts on individual perceptions—specifically, study participants preferred gaining $1 on one occasion to gaining 50 cents over two occasions and preferred losing $1 one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 92 publications
1
24
1
1
Order By: Relevance
“…Previous research has found that customers tend to be relatively dissatisfied with long waiting time compared with short waiting time generally (Taylor, 1994;Lee et al, 2012;Lin et al, 2015). Customers also tend to be dissatisfied with waiting duration for service delivery where they are uncertain about waiting time, when they do nothing during waiting, when they are with a group, when there are no explanations, apology or compensations for perceived unacceptable waiting durations (Bae and Kim, 2014;Antonides et al, 2002;Kumar et al, 1997).…”
Section: Waiting Time Satisfaction (Wts)mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has found that customers tend to be relatively dissatisfied with long waiting time compared with short waiting time generally (Taylor, 1994;Lee et al, 2012;Lin et al, 2015). Customers also tend to be dissatisfied with waiting duration for service delivery where they are uncertain about waiting time, when they do nothing during waiting, when they are with a group, when there are no explanations, apology or compensations for perceived unacceptable waiting durations (Bae and Kim, 2014;Antonides et al, 2002;Kumar et al, 1997).…”
Section: Waiting Time Satisfaction (Wts)mentioning
confidence: 99%
“…The importance of customer waiting time management lies in the fact that customers' perception of waiting time of service providers could affect their current and future relationship with service providers (Lerclec et al, 1995;Lin et al, 2015;Palawatta, 2015). This prception means that when customers are satisfied with the amount of time they wait for services, it can induce loyalty behaviours in customers and influence them to desire more future business with service providers.…”
Section: Put Itmentioning
confidence: 99%
See 3 more Smart Citations